A Case Report of Clobazam Toxicity Related to Cannabidiol and Clobazam Drug-drug Interaction (Translation: The University of Toledo Journal of Medical Sciences, 2019)
The interest in the anti-seizure efficacy of cannabinoids (CBD)has significantly increased over the past decade. Trials have shown a remarkable reduction in the frequency of convulsive seizures in Dravet and Lennox-Gastaut syndromes patient population. Studies have shown that CBD reacts with Clobazam leading to a significant increase in the levels of N-desmethylclobazam, the active metabolite of Clobazam. We present a case of a patient with Dravet syndrome who presented to the emergency department with altered mental status secondary to Clobazam toxicity related to CBD and Clobazam drug-drug interaction. We present a case of a patient with Dravet syndrome who presented to the emergency department with altered mental status. Patient was hospitalized and Clobazam was held off. Clobazam level and N-desmethylclobazam levels were obtained and came back elevated at 512 ng/mL and 15020 ng/mL respectively (reference range 30-300 ng/mL and 300 to 3000 ng/mL respectively).Rowida Kheireldin (a) (1) Naeem Mahfooz (b)
Keywords: Epidiolex; Clobazam; Dravet syndrome; LennoxGastuat syndrome